Interaction of Life Cycle Assessment (LCA) and BIM in a Construction Project to Reduce the Environmental Footprint - Osorio-Gómez, Cristian C.; Alzate-Buitrago, Alejandro; Amariles-López, Cristhian C.; Aristizábal-Torres, Daniel; Mancilla-Rico, Edwin A. (Salehan Institute of Higher Education, 2025)
The construction sector is experiencing rapid growth in response to the increasing demand for new projects that address societal needs, making it one of the most significant contributors to greenhouse gas emissions. Therefore, it is essential to develop more sustainable and efficient construction processes that reduce the environmental impact in the sector. This study focuses on assessing the environmental footprint of a residential project in Colombia, based on the implementation of Building Information Modeling (BIM) with a sustainability focus. A Life Cycle Assessment (LCA) was performed using the